FILM ANIMASI 2D CERITA RAKYAT â€œBATU NEK JAGOâ€ DI KECAMATAN TEBAS - Seli Seselia; Mega Fina Alviany; Narti Prihartini; Uray Heri Mulyanto (PROGRESS, 2023)
Folklore is a story that develops in society and Delivered through generations which contains moral messages and values from every characters. Technology and information capabilities that are very rapid demand an increase in competence, one of which is an increase in literacy competence. Base on Indonesian literacy, an UNESCO study entitled The Most World's Literate Nations in 2017 released Indonesia's 60th ranking in reading interest. People prefer to watch videos rather than read writing, this happens because videos seem more interesting than stories that only contain text. The test was carried out with a questionnaire given to material experts, media experts, and 40 respondents to find out whether the "2 Dimensional Animation Video of the folklore of Batu Nek Jago" is appropriate for publication. The test results show that in the questionnaire media experts are 78%, material experts are 88%, and respondents are 65.5% or it can be concluded that "Animated Film 2 Dimensions of the folklore Batu Nek Jago" Sambas is worthy of publication.